Germany’s NetzDG: Template for Dealing with Fake News? - Jayakumar, Shashi (2018)
The German Netzwerkdurchsetzungsgesetz, also known as the NetzDG or Network Enforcement Act (NEA), came into effect last October, with actual enforcement commencing in January 2018. Is this the Fake News silver bullet that Singapore and other nations should be considering?